(untitled) (Medicine Today, 2017)
Fahr’s syndrome refers to a rare syndrome characterized by symmetrical and bilateral intracranial calcification. We present a 65-year-old female with Fahr disease, presenting with headache with acute ischaemic stroke with left sided hemiplegia. CT scan of brain reveals irregular variable size hyperdense areas are noted in both basal ganglia regions and in both cerebellar hemisphere. Medicine Today 2017 Vol.29(1): 45-46